Університет і його музеї: місце у культурному і туристичному просторі міста - Муравська, С. (Місто: історія, культура, суспільство, 2017)
У статті авторка робить спробу проаналізувати, яке місце заклад вищої освіти загалом та його музеї зокрема відіграють у житті міста. Емпіричною основою статті є інформація, зібрана в результаті дослідницьких візитів до ЗВО семи областей: Львівської, Івано-Франківської, Тернопільської, Волинської, Рівненської, Чернівецької та Закарпатської, які виконувалися упродовж 2013-2017 рр. Основний метод, який використовувався – інтерв’ю з персоналом музеїв ЗВО. Зокрема, характеризується нетипова для українського контексту роль музеїв ЗВО як «вікон» та «вітрин», завдяки яким представники позаакадемічного середовища можуть ознайомитися із здобутками вищої школи та відчути її особливу атмосферу. Авторка окреслює туристичний потенціал низки ЗВО на теренах Західної України, фізичні об’єкти яких є цікавими з архітектурної та культурної точки зору пам’ятками. Проведення відповідної політики, як стосовно музеїв, так і академічного простору загалом, дозволить закладу стати окремою точкою на туристичній карті міста, налагодити взаємозв’язки із навколишньою громадою, активно брати участь у локальному культурному житті. Такі кроки сприятимуть зростанню його популярності серед абітурієнтів і розвитку реноме ЗВО загалом. The article attempts to analyze the place of higher educational establishments (HEE) in general and its museums in particular playing in the city life. The empirical basis of the article is the information collected as a result of research visits to HEE in seven regions of Western Ukraine: Lviv, Ivano-Frankivsk, Ternopil, Volyn, Rivne, Chernivtsi and Zakarpattia, organized for 2013-2017. The main used method is interviews with personnel of HEE museums. The author points out these «temples of muses» gradually moved away from its traditional educational and research mission in the 1980’s. Such reassessment of priorities had been caused by the crisis of the museum. For the last 30 years it has become clear reduction of using the collections for teaching and research in many universities; some HEE plan to dispose collections and to close museums; many universities are working out alternative organizational models for managing collections in the one newly created museum. The crisis in the museum environment has imposed on the crisis, which the parent universities as institutions are encountering today - «crisis of identity » and «a crisis of resources», caused by the increasing often contradictory requirements to the high schools. On this background the museums as individual units also began to increase requirements. It let to their gradual transformation into a museum of «third generation». One of their defining mission is promoting the HEE, cooperation with the public in order to disseminate information about the university, vocational guidance, involvement of patrons and organization of other works implementing this direction. In particular, the article highlights atypical for the Ukrainian context the role of HEE museums - «shop-windows» and «show-cases», through which representatives of outside universty environment can acquaint themselves with the achievements of high school and feel its special atmosphere. The author outlines a number of touristic potential of some HEE in Western Ukraine, where physical objects are interesting from an architectural and cultural point of view. Among the most striking examples are the main building of Yuriy Fedkovych Chernivtsi National University., Ivan Franko National University of Lviv, campus of Lviv Polytechnic National University, campus of The National University of Ostroh Academy, Lviv State University of Life Safety, Kremenets Forestry College. Among the researched 74 HEE are roughly a quarter which can be classified as «visually attractive». However, less than 10 % of them use this advantage for brand developing. The relevant policy concerning museums and academic space in general will allow high school to become a separate point on the tourist map, to establish relationships with the surrounding community and to participate actively in local cultural life.